Valuation and risk management in energy markets - Swindle, Glen (Cambridge : Cambridge University Press, 2014)
Valuation and Risk Management in Energy Markets surveys the mechanics of energy markets and the valuation of structures commonly arising in practice. The presentation balances quantitative issues and practicalities facing portfolio managers, with substantial attention paid to the ways in which common methods fail in practice and to alternative methods when they exist. The material spans basic fundamentals of markets, statistical analysis of price dynamics, and a sequence of increasingly challenging structures, concluding with issues arising at the enterprise level. In totality, the material has been selected to provide readers with the analytical foundation required to function in modern energy trading and risk management groups.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Energy industries -- Finance; Commodity futures; Investments -- Mathematical models; Financial risk